Kepemilikan Ultimat, Tingkat Risiko, Efisiensi dan Kinerja Industri Perbankan di Indonesia - Surifah Surifah (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2011)
AbstractThe research empirically verified the effect of ultimate ownership on industrial banking performance in Indonesia. Risk rate, efficiency, and general performance serve as proxy for bank performance. Based on multiple-regression test and Kruskal-Wallis test, the performance rank in terms of risk rate, efficiency and general banking performance were as follows, (1) mixed foreign and domestic banks, (2) foreign banks, (3) local governmental banks, (4) Indonesian national governmental banks, (5) family banks, (6) concentrated private banks, and (7) block shareholding private insititutions. The percentage of the ultimate ownership did not affect the risk rate, efficiency and general banking performance; but significantly and positively affected profit growth. The bank size has negative effect on the risk indicator, ETA and CAR. The bank size negatively affected BOPO. The bank size positively affects on DEA meaning bigger bank is more efficient. Bank did not significantly differ in general performance – which was measured with ROA and profit growth – but significantly and positively affected ROE.Keywords: ultimate ownership, risk, efficiency, performanceAbstrakPenelitian ini secara empiris memverifikasi pengaruh kepemilikan ultimat pada kinerja industri perbankan di Indonesia. Berdasarkan uji regresi berganda dan Kruskal-Wallis, peringkat kinerja dalam hal tingkat resiko, efisiensi dan kinerja perbankan secara umum adalah sebagai berikut (1) bank asing dan domestik digabung, (2) bank asing, (3) bank pemerintah daerah, (4) bank pemerintah nasional, (5) bank keluarga, (6) bank swasta terkonsentrasi, dan (7) kepemilikan saham institusi swasta. Persentase kepemilikan akhir tidak mempengaruhi tingkat resiko, efisiensi dan kinerja perbankan secara umum, tetapi secara signifikan dan positif mempengaruhi pertumbuhan laba. Ukuran Bank memiliki efek negatif pada indikator risiko, ETA dan CAR. Ukuran Bank secara negatif mempengaruhi BOPO. Ukuran Bank secara positif mempengaruhi DEA. Bank tidak berbeda secara signifikan dalam kinerja umumnya yang diukur dengan ROA dan pertumbuhan laba, tetapi kinerja ini secara signifikan dan positif mempengaruhi ROE.Kata kunci: kepemilikan akhir, risiko, kinerja, industri perbankan, efisiensi